2003
DOI: 10.1113/jphysiol.2003.045872
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis inhibits oxidative phosphorylation in contracting human skeletal musclein vivo

Abstract: This study tested the hypothesis that acidic pH inhibits oxidative ATP supply during exercise in hand (first dorsal interosseus, FDI) and lower limb (leg anterior compartment, LEG) muscles. We measured oxidative flux and estimated mitochondrial capacity using the changes in creatine phosphate concentration ([PCr]) and pH as detected by 31P magnetic resonance (MR) spectroscopy during isometric exercise and recovery. The highest oxidative ATP flux in sustained exercise was about half the estimated mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
128
1
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(151 citation statements)
references
References 38 publications
12
128
1
10
Order By: Relevance
“…Intracellular pH level at 70%MVC was 6.93 ± 0.01 (ranging from 6.80 to 7.03). This is the upper level of intracellular acidosis (pH = 6.8) on oxidative phosphorylation as shown in previous studies (Conley et al 2001;Jubrias et al 2003). This result suggests that the effect of intracellular acidosis at 70%MVC was greater than at a lower %MVC.…”
Section: The Availability Of Intramuscular O 2 During Isometric Exercsupporting
confidence: 64%
See 1 more Smart Citation
“…Intracellular pH level at 70%MVC was 6.93 ± 0.01 (ranging from 6.80 to 7.03). This is the upper level of intracellular acidosis (pH = 6.8) on oxidative phosphorylation as shown in previous studies (Conley et al 2001;Jubrias et al 2003). This result suggests that the effect of intracellular acidosis at 70%MVC was greater than at a lower %MVC.…”
Section: The Availability Of Intramuscular O 2 During Isometric Exercsupporting
confidence: 64%
“…This result suggests that the effect of intracellular acidosis at 70%MVC was greater than at a lower %MVC. However, previous studies reported that relatively mild acidosis (pH 6.8-6.9) prevented a rise in oxidative flux despite a substantial rise in ADP (Jubrias et al 2003). Thus, this mild acidosis at 70%MVC might also attenuate the availability of intramuscular O 2 in muscle.…”
Section: The Availability Of Intramuscular O 2 During Isometric Exercmentioning
confidence: 80%
“…Secondly, many enzyme activities related to ATPase and glycolysis are affected by the pH. However, mitochondrial enzymes are not affected (89), although recent works came to a different conclusion in studies of human (90) and cat (91) muscles. Reducing ADP by low pH [eqn (1)] actually suppresses the mitochondrial respiration.…”
Section: Anaerobic Glycolysismentioning
confidence: 90%
“…The TA muscle is important in ankle dorsiflexion and represents a simple system connecting muscle mechanics and energetics to foot movement30 and is a critical part of walking mobility. The subject performed a maximal voluntary contraction (MVC) using ankle dorsiflexion for ~5 sec by pulling on a strap that secured the foot to a force transducer platform.…”
Section: Methodsmentioning
confidence: 99%